Quality Management In Healthcare: Enhancing Patient Outcomes (Journal of Namibian Studies : History Politics Culture, 2023)
Quality management is a fundamental aspect of healthcare delivery, aimed at optimizing patient outcomes and ensuring the safety and satisfaction of individuals receiving medical care. This paper explores the significance of quality management in healthcare settings and examines strategies and initiatives designed to enhance patient outcomes. Key principles of quality management, including patient-centered care, continuous improvement, and interdisciplinary collaboration, are discussed. Additionally, the paper highlights the importance of evidence-based practice and the role of technology and innovation in advancing quality management efforts.